2003
DOI: 10.2355/isijinternational.43.1781
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and Annealing Behavior of Nitrogen Alloyed Duplex Stainless Steels. Part I: Rolling

Abstract: Fig. 7. Cold rolling textures of the austenite phase of DSS 1 and DSS 4 and of a single phase (Cu37%Zn) brass (90 % thickness reduction).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 7 publications
5
63
0
1
Order By: Relevance
“…Before precipitates could develop the temperature in the material had already reached 1 050°C, which is slightly higher than the homogenization temperature, where the phase fractions are stable. 1) Consequently, DSS 5 which had the largest austenite phase fraction and grain size and additionally the highest nitrogen content, was not affected by precipitation during slow heating. This stresses the impor- tant influence of the microstructure dimensions on diffusion controlled microstructure development, e.g.…”
Section: Microstructure Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before precipitates could develop the temperature in the material had already reached 1 050°C, which is slightly higher than the homogenization temperature, where the phase fractions are stable. 1) Consequently, DSS 5 which had the largest austenite phase fraction and grain size and additionally the highest nitrogen content, was not affected by precipitation during slow heating. This stresses the impor- tant influence of the microstructure dimensions on diffusion controlled microstructure development, e.g.…”
Section: Microstructure Evolutionmentioning
confidence: 99%
“…While the high heating rate of the salt bath annealing allowed softening to proceed without being influenced by precipitates, the conventionally annealed samples experienced some phase transformations and precipitates of a-phase, c-phase and CrN 2 nitrides because the temperature versus time profile T(t) crossed TTT curves. The annealing temperatures of 1 050°C and 1 100°C were chosen to enable long annealing times without the influence of pre-Jörg KEICHEL, Jacques FOCT 1) and Günter GOTTSTEIN The softening behavior of ferritic-austenitic duplex stainless steels (DSS) was investigated separately for both phases by means of microstructure investigations and texture analysis. The results were compared to those of similar single phase materials in order to unveil the influence of the second phase on the specific softening mechanisms during annealing after cold rolling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results for hot-rolling textures of the and phases in DSS sheet were the same as for the rolling textures of bcc and fcc metals, respectively, and were similar to the previous results. [7][8][9]23) Figure 7 shows the ' 2 ¼ 45 sections of the ODFs measured in the hot-rolled and annealed sheets. After annealing at 1050 C (a) and (b), in the phase (a) there was still a strong presence of -fiber, and the texture of the phase (b) was about the same as the texture in hotrolled sheet.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6][7] However, the mechanism is not clear, and there have been few studies on the characteristics of microstructure and texture in hot rolling, cold rolling, and annealing. [8][9][10] In addition, the microstructural evolutions in ( þ ) microduplex stainless steel caused by thermo-mechanical processing, which combines deformation and heat treatment, were investigated. [11][12][13][14][15][16][17][18][19][20][21] Huang et al [14][15][16] showed that no recrystallization of the matrix took place when the initial structure before cold rolling was fine, but recrystallization occurred in the matrix with f111gh011i initial orientation when the initial structure was coarse.…”
Section: Introductionmentioning
confidence: 99%